Failure of papyerine hydrocholoride and doxycycline hyclate as antipruritis agents in pruritic dogs: Results of an open clinical trial - Scott, Danny W. (1993)
Papaverine hydrochloride (150 to 300 mg/dog every 12 hours) and doxycycline hyclate (3 mg/kg every 12 hours) were both administered orally as individual agents to 13 dogs with pruritus of allergic or idiopathic origin. No dog improved. Depression, anorexia, and vomiting were seen in one dog treated with papaverine hydrochloride. Under the conditions of the study, papaverine and doxycycline were not useful antipruritic agents for the dog.